تمثلات الفضاء الحضري بوادي ريغ - باعيسى مبروكة; شين سعيدة (University Of Eloued جامعة الوادي, 2023)
الملخص: تهدف هذه الورقة البحثية إلى تسليط الضوء على دراسة تمثلات فضاء منطقة وادي ريغ؛ التي تعد أحد أهم الفضاءات الحضرية الواقعة بالجنوب الشرقي الجزائري، من خلال التركيز على دراسة كيفية تمثل سكان هذه المناطق لفضاءاتهم الحضرية؟ وحتى نجيب على هذا التساؤل تطرقنا إلى معرفة تاريخ المنطقة، وأنواع الفضاءات الحضرية المتواجدة بها وكيف تشكلت عبر الزمن، لنصل إلى عدد من النتائج لعل أهمها: أن منطقة وادي ريغ تنقسم إلى قسمين، فضاء عام وفضاء خاص، ولكل فضاء منهما خصوصية ما، حيث تمارس فيه أي خصوصية تميزه عن الفضاءات الأخرى من خلال الممارسات اليومية التي تتم ضمنه، وكيف يتم التعامل ضمن كل فضاء من خلال الحدود التي يرسمها في أذهان من يترددون إليه. وعليه يمكن القول: إن تمثلات فضاء منطقة وادي ريغ تتميز بتعدد تمثلاته من دينية وثقافية، واقتصادية واجتماعية، تحمل في طياتها دلالات ورموزا متنوعة ذات العلاقة بهذا الفضاء المتميز. This research paper aims to shed light on the study of representations of the space of Oued Righ region; which is one of the most important urban spaces located in the southeast of Algeria, by focusing on studying how the inhabitants of these areas represent their urban spaces? In order to answer this question, we touched on knowing the history of the region, the types of urban spaces present in it, and how they were formed over time, to reach a number of results, perhaps the most important of which is: The Oued Righ region is divided into two parts, a public space and a private space, and each space has some specificity, as it is practiced It has any privacy that distinguishes it from other spaces through the daily practices that take place within it, and how dealing is done within each space through the borders that it draws in the minds of those who frequent it. Accordingly, it can be said: The representations of the space of the Oued Righ region are characterized by the multiplicity of its religious, cultural, economic and social representations, which carry with it various connotations and symbols related to this distinct space. independence.
Keywords: تمثلات; الفضاء الحضري; أنثروبولوجيا الفضاءات الحضرية; وادي ريغ; representations; urban space; anthropology of urban spaces; Oued Righ